2020
DOI: 10.1186/s12974-020-01939-6
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal interleukin-33 mediates neuroinflammation-induced cognitive impairments

Abstract: Background Interleukin (IL)-33 is expressed in a healthy brain and plays a pivotal role in several neuropathologies, as protective or contributing to the development of cerebral diseases associated with cognitive impairments. However, the role of IL-33 in the brain is poorly understood, raising the question of its involvement in immunoregulatory mechanisms. Methods We administered recombinant IL-33 (rmIL-33) by intra-hippocampal injection to C57BL/6 J (WT) and IL-1αβ deficient mice. Chronic minocycline admin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Carlock et al [ 51 ] in 2017 pointed out that deficiency of IL-33 caused tau abnormality and late-onset neurodegeneration in the cerebral cortex and hippocampus, accompanied by memory impairment. A recent study suggested that IL-33 gene mutations affect susceptibility to late-onset AD, which in turn confirms that IL-33 may exacerbate neuroinflammation and cognitive decline[ 52 , 53 ].…”
Section: Il-33 Role In Neuroinflammation and Neurodegenerationmentioning
confidence: 88%
“…Carlock et al [ 51 ] in 2017 pointed out that deficiency of IL-33 caused tau abnormality and late-onset neurodegeneration in the cerebral cortex and hippocampus, accompanied by memory impairment. A recent study suggested that IL-33 gene mutations affect susceptibility to late-onset AD, which in turn confirms that IL-33 may exacerbate neuroinflammation and cognitive decline[ 52 , 53 ].…”
Section: Il-33 Role In Neuroinflammation and Neurodegenerationmentioning
confidence: 88%
“…In the newborn brain with Zika virusinduced microcephaly, IL-33 is significantly upregulated compared to that in newborn brains with microcephaly without virus infection (78,79). IL-33 has been found to positively correlate with IL-1b expression (79,80), implying that IL-33 might play a role in the proinflammatory response in virus infection. In addition, an in vitro study demonstrated that HIV infection induces IL-33 release from neurons and ST2 upregulation in astrocytes.…”
Section: Il-33 In Infectionmentioning
confidence: 99%
“…A representative example is provided by IL-33, a member of the IL-1 family that showed either neuroprotective or neurodegenerative effects in different experimental conditions. Intraperitoneal injections (50 mg/kg, about 1.15 mg per animal, 10 days) followed by intrahippocampal injection (400 ng by side) of IL-33 in 8-week-old mice, evoked neuroinflammation and cognitive impairment [ 170 ], whereas intraperitoneal injections (200 ng, 7 days) of IL-33 in transgenic mouse models of AD (mice, 48 weeks old) mobilized microglia to prevent and clear Aβ-deposits, thus ameliorating cognitive impairment [ 171 ]. Of note, IL-33 released by astrocytes has been suggested to modulate typical microglia activities such as the pruning of synapses in mouse embryos during maturation [ 50 ] and modulation of synaptic plasticity in adult mice (16 weeks old) [ 104 ].…”
Section: Interactions Between Microglia and Astrocytesmentioning
confidence: 99%